Kampanye Iklan Layanan Masyarakat Produksi PNRI - Laksmi, Laksmi (UI Scholars Hub, 2010)
This study examines the message of the public services announcement (PSA) produced by PNRI. The PSA are supposed to encourage audiences to read books to improve their live. Indonesian society is known as oral tradition, meanwhile, reading habit helps people develop a critical thinking. I use qualitative approach to analyze dialogues, characters, virtual images, and information. The aim of the study is to understand how PSA is produced, communicated, and consumed by people. This research analyses meaning construction of reading and its relevance to welfare. I collect the data from seven PSA and analyze them by critical discourse analysis method. The first finding is that people understand partially the message: they understand that library and reading are important for their life. But they do not understand the relevancy between reading and improving their live. Second finding, most of society belief that they learn knowledge not necessary from the books, but they can gain it from parents, friends, religion, and television. Meanwhile, PSA reveals social reality that there are different values between society and PNRI. The contradictions of values become barriers to deliver the message of the importance of reading. The recommendation for it is to improve technique of campaign.